SAT-217 A Spontaneous and Uneventful Pregnancy in a Turner Syndrome Patient with 45,X[22]/46,X,+Mar[2]/46,Xx[1] Mosaicism: Case Report and Literature Review - Scalco, Renata (J Endocr Soc, 2019)
Case report: Our patient was first evaluated at 5 years old (yo) because of short stature (height standard deviation score (SDS) -2.4) and recurrent acute otitis media. Her karyotype was 45,X and she did not have cardiac or renal malformations. She was treated with oxandrolone 0.0625 mg/kg/d for 20 months starting at chronological age (CA) 9y 8mo and then with growth hormone (GH) 50 µg/kg/d for 3 years starting at 12 yo, reaching an adult height of 146 cm. She had spontaneous thelarche with CA 11y 11mo and spontaneous menarche at 14y 6mo of age. Her menstrual periods, which were initially regular, became irregular and at 19 yo she started to use contraceptive pills to regulate them. She got married at 25 yo and adopted her first daughter when she was 29 yo. Since her LH and FSH had always been normal before anticonceptional use and became suppressed after its start, we discontinued it when she was 29 yo to reevaluate her ovarian function and asked for a new karyotype. Her LH, FSH and her menstrual periods went back to normal and she decided to try for a spontaneous pregnancy. Cardiac /aortic MRI was normal and pregnancy was allowed. Her new karyotype was 45,X[22]/46,X,+mar[2]/46,XX[1] and Y chromosomal material was not detected. At 32 yo she became pregnant. Standard blood examination and first trimester ultrasonography were performed without abnormal findings. She was then monitored by a high-risk pregnancy team and cardiologist. At 38 weeks of gestation, a cesarean section was performed because of cephalopelvic disproportion. She delivered a healthy female infant with a 46,XX karyotype. Literature review: More than a 100 cases of spontaneous pregnancies in patients with Turner syndrome (TS) were reported in literature. These patients had spontaneous thelarche and menarche and most of them had mosaicisms involving a 46,XX lineage, although there are reports of spontaneous pregnancies in patients with 45,X monosomy, isochromosome or ring X and mosaicisms for other cell lineages. Most newborns have a normal 46,XX or 46,XY karyotype and no abnormalities in physical examination. However, there is a higher risk of miscarriage especially during the first trimester of gestation (between 30 and 45%) and a higher prevalence of Turner syndrome in the offspring. Furthermore, other unfavorable outcomes apparently unexplained by the presence of Turner syndrome in the mother were described such as Down syndrome, atypical genitalia, cerebral palsy, hydrocephalus, cleft lift and palate and congenital tumors. There are also risks for the mother, especially involving pregnancy-induced hypertensive disorders, which can increase the risk of aortic dissection, but also a higher risk of gestational diabetes. Conclusion: Spontaneous pregnancies in TS patients occur mainly in patients with mosaicisms and should be monitored by obstetricians and cardiologists with experience in dealing with these patients.